miRNA heterologous production in bacteria: A systematic review focusing on the choice of plasmid features and bacterial/prokaryotic microfactory - da Silva Nonato, Nyelson; Nunes, Leandro Silva; da Silveira Martins, Amanda Weege; Pinhal, Danillo [UNESP]; Domingues, William Borges; Bellido-Quispe, Dionet Keny; Remião, Mariana Härter; Campos, Vinicius Farias (Elsevier, 2024)
Bacteria, the primary microorganisms used for industrial molecule production, do not naturally generate miRNAs. This study aims to systematically review current literature on miRNA expression systems in bacteria and address three key questions: (1) Which microorganism is most efficient for heterologous miRNA production? (2) What essential elements should be included in a plasmid construction to optimize miRNA expression? (3) Which commercial plasmid is most used for miRNA expression? Initially, 832 studies were identified across three databases, with fifteen included in this review. Three species—Escherichia coli, Salmonella typhimurium, and Rhodovulum sulfidophilum—were found as host organisms for recombinant miRNA expression. A total of 78 miRNAs were identified, out of which 75 were produced in E. coli, one in R. sulfidophilum (miR-29b), and two in S. typhimurium (mi-INHA and miRNA CCL22). Among gram-negative bacteria, R. sulfidophilum emerged as an efficient platform for heterologous production, thanks to features like nucleic acid secretion, RNase non-secretion, and seawater cultivation capability. However, E. coli remains the widely recognized model for large-scale miRNA production in biotechnology market. Regarding plasmids for miRNA expression in bacteria, those with an lpp promoter and multiple cloning sites appear to be the most suitable due to their robust expression cassette. The reengineering of recombinant constructs holds potential, as improvements in construct characteristics maximize the expression of desired molecules. The utilization of recombinant bacteria as platforms for producing new molecules is a widely used approach, with a focus on miRNAs expression for therapeutic contexts.
Keywords: Bioengineered RNA; Bioengineering; Genetic engineering; miRNA expression systems; Non-coding RNAs; Therapeutics